Weight-adjusted-waist index is positively associated with fecal incontinence: a cross-sectional study - Ying Zhang; Wenting Hu; Zhilian Zhou; Xiuming Wang; ChanChan Lin (Journal of Health, Population and Nutrition)
Abstract Introduction Fecal incontinence (FI), a prevalent condition affecting approximately 7.7% of the global population and 8.3% of Americans, significantly impairs quality of life. Although FI is closely associated with obesity, the specific impact of weight-adjusted waist index (WWI) on FI remains unclear. This study aimed to investigate the association between this novel anthropometric indicator, WWI, and FI among American adults. Methods This cross-sectional study enrolled 12,922 participants from the National Health and Nutrition Examination Survey (NHANES). WWI was calculated as waist circumference (cm) divided by the square root of weight (kg). FI was defined as any involuntary loss of mucus, liquid, or solid stool in the past month, assessed via the NHANES Bowel Health Questionnaire. Weighted multivariable logistic regression analyses were performed to evaluate the association between WWI and FI. Furthermore, we utilized smoothing curve fitting to elucidate potential linear relationships. The predictive performance of WWI, body mass index (BMI), and waist circumference (WC) in relation to FI was assessed using the receiver operating characteristic curve analysis and DeLong’s non-parametric test. Results The overall prevalence of FI was 8.14%. Weighted multivariable logistic regression analyses indicated that each one-unit increase in WWI was associated with a 36% higher prevalence of FI (OR = 1.36, 95% CI:1.20–1.55; P < 0.001). When WWI was categorized into tertiles and compared to the lowest tertile, the highest tertile maintained a positive association with FI (OR = 1.63, 95% CI:1.31–2.02; P < 0.001). Smoothing curve fitting revealed a linear dose–response relationship between WWI and FI. Subgroup analysis indicated no significant interactions (all P > 0.05). Additionally, our results suggested that the correlation between WWI and FI was stronger than that between BMI or WC and FI. Conclusions WWI is independently associated with FI, suggesting its potential utility in clinical assessment. WWI may refine risk stratification in obesity management strategies.